Linking Fruit Ca Uptake Capacity to Fruit Growth and Pedicel Anatomy, a Cross-Species Study - Song, Wenpei; Yi, Junwen; Kurniadinata, Odit F.; Wang, Huicong; Huang, Xuming (Frontiers in Plant Science, 2018)
Calcium (Ca) in flesh fruits is important for quality formation and maintenance. Most studies on fruit Ca focus on one species. This study attempted to understand some universal relations to fruit Ca uptake across species. Calcium contents in fruit tissues were analyzed in different fruits, including three cultivars of litchi, two cultivars each of grape and citrus, and one cultivar each of loquat, apple, pear, Indian jujube and longan. In situ Ca distribution was revealed with electron probe and xylem functionality visualized by dye tracing. Fruit Ca uptake rate and activity were calculated and correlated with fruit growth and pedicel anatomy. The results showed that fruit Ca uptake rate was the highest in pomes (loquat, apple and pear), followed by Indian jujube drupe, arillate fruits (litchis and longan) and citrus, while grape berries were the lowest. Fruit Ca uptake rate showed a strong positive correlation to growth rate. However, Ca uptake activity, reflecting Ca uptake rate relative to growth, was the highest in arillate fruits and loquat and lowest in grape berries, and had a poor correlation with fruit growth rate. In all fruits, Ca concentration in the pedicel was higher than in the fruit, and they displayed a good positive correlation. In the pedicel, Ca was most abundant in the phloem. Dye tracing showed that xylem function loss occurred with maturation in all species/varieties. Apple had the poorest xylem functionality with the least development of secondary xylem, but its Ca uptake rate was among the highest. Vessel density, size and area in the pedicel showed no correlation with fruit Ca uptake rate. It is concluded that: (1) fruit growth may be a key determinant of Ca uptake; (2) the universal pattern of Ca being higher in the pedicel than in the fruit indicates existence of a pedicel-fruit “bottleneck” effect in Ca transport across species; (3) xylem functionality loss with fruit maturation is also a universal event; (4) in the pedicel, Ca is more distributed in the phloem; (5) vessel morphology in the pedicel is not rate-limiting for fruit Ca uptake; (6) phloem pathway might contribute to fruit Ca uptake.